Adaptation to the degradation of natural resources in the semiarid area of Mexico (Sustainability in Debate, 2010)
Hydrology and soil research in the semiarid zone of Mexico highlight an erosion process that is worsened by climate and land use changes. Scientific results have inspired a successful adaptation program with an environmental and socioeconomic scope. The Hydrological Environmental Services Programm.e (PSAH, in Spanish) pays local workers to build soil and water conservation infrastructure in areas with the potential to provide hydrological environmental services. The programme’s results are still under assessment, but some qualitative results may be already identified: soil and water retention, plant cover recovery, permanence of local people in their comm.unities, and social welfare, among others. The PSAH as a strategy should be echoed in other places of Mexico in order to replicate their benefits on the physical and human environments of the semiarid zone.